Carrier-Envelope Offset Frequency Stabilization of a Thin-Disk Laser Oscillator via Depletion Modulation - Jose R. C. Andrade; Norbert Modsching; Ayhan Tajalli; Christian M. Dietrich; Sven Kleinert; Fabian Placzek; Bernhard Kreipe; Stephane Schilt; Valentin J. Wittwer; Thomas Sudmeyer; Uwe Morgner (IEEE Photonics Journal, 2020)
We present a novel concept for the stabilization of the carrier-envelope offset (CEO) frequency of femtosecond pulse trains from thin-disk laser oscillators by exploiting gain depletion modulation in the active gain region. We shine a small fraction of the laser output power back onto the thin disk allowing the population inversion in the gain medium to be controlled. We employ this technique in our home-built Kerr-lens mode-locked Yb:YAG thin-disk laser and benchmark the performance against the proven technique of pump current modulation for CEO stabilization, showing that the two techniques have equivalent performance. The new method which only requires an additional AOM demonstrates a scalable and cost-effective method for CEO stabilization of high-power laser oscillators.